Adaptive Leadership and The Gen-Z Mindset: Driving the Adoption of Work Culture for Organizational Sustainability - Andrilla, Riska; Saputra, Dasriyan (Ilomata International Journal of Management, 2026)
This study examines the influences of adaptive leadership on Gen Z's mindset in adopting work culture and promoting organizational sustainability. Integrating traditional leadership with Gen Z’s mindset is increasingly critical as Balikpapan's industrial sector undergoes a generational shift. This research will explore the challenges of aligning Gen Z’s mindset with strategies that sustain organizational effectiveness in dynamic cultures. Specifically, it examines how adaptive leadership shapes Gen Z’s mindset and acceptance of workplace culture, promoting organizational sustainability. This study uniquely provides empirical evidence on the mediating role of the Gen Z mindset within the adaptive leadership and sustainability framework in a developing economy, emphasizing the intergenerational connection between leadership and organizational culture. A mixed-methods approach was employed, involving 208 Gen Z employees in Balikpapan and utilizing both quantitative data and qualitative interviews. Analyses included Cronbach's Alpha, composite reliability, and structural equation modelling using partial least squares (SEM-PLS). The findings indicate that adaptive leadership significantly influences Gen Z mindset and work culture adoption. Furthermore, the Gen Z mindset mediates the relationship between corporate culture and leadership, which is essential for sustainability, although it does not directly affect sustainability. Conclusion: Adaptive leadership empowers and involves Gen Z, promoting lasting organizational and cultural transformation. The findings offer HR specialists and business leaders insights to foster intergenerational relationships and boost organizational effectiveness.